Analisis Framing Model Zhongdang Pan dan Gerald M. Kosicki Terhadap Pemberitaan Peringatan Hari Guru Nasional 2024 pada Media Online Sokoguru.Id dan Mediaindonesia.Com - Layung Siti Nurazizah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Mass media serves as a vital communication medium that delivers crucial information to the public. In the digital era, technological advancements have facilitated easier access to news for audiences. This study aims to analyze the framing of the 2024 National Teacher’s Day coverage on the online media platforms sokoguru.id and mediaindonesia.com. Using a qualitative approach guided by Zhongdang Pan and Gerald M. Kosicki’s framing analysis model, this research uncovers how each outlet portrays the theme “Great Teachers, Strong Indonesia.” The findings reveal differing approaches: sokoguru.id focuses on tangible issues like teacher welfare and technological training, while mediaindonesia.com emphasizes symbolic tributes to teachers through celebratory narratives. Both platforms employed the inverted pyramid style in organizing their news and adhered to the 5W+1H elements. However, differences emerged in their thematic and rhetorical structures. This study highlights how media framing influences public perception of educational issues and underscores the importance of teacher welfare in building a high-quality education system.